A Stormy War of Position: An Investigation of the Use of Human Right to Water and Sanitation Discourse to Legitimate Accumulation by Dispossession - Karunananthan, Meera (Université d'Ottawa / University of Ottawa, 2015)
This thesis examines the corporate appropriation of human right to water and sanitation discourse. David Harvey’s concept of accumulation by dispossession provides the political- economic basis for this analysis while enabling a discussion of water conflicts that looks at neoliberalization strategies beyond the privatization of services. Inspired by Gramsci’s notion of a “war of position”, this thesis investigates the role of corporate appropriation of human right to water and sanitation discourse in legitimating strategies of accumulation by dispossession. Through content and critical discourse analysis of publications of a corporate policy consortium called the 2030 Water Resources Group the investigation concludes that this lobby group simultaneously undermines human rights while actively using key elements of rights discourse to advance its neoliberal water policy objectives.
Keywords: accumulation by dispossession; human right to water; Harvey; Gramsci